Motor Board : Type 5130 - Technical Description - Hps SystemTechnik
The Motor board contains a machine set with the following components: DC motor with current actual value acquisition. DC generator with connectable load. Tachogenerator with decoupling amplier. Connectable mechanical centrifugal mass. Dual - channel angle encoder for regconition of speed and direction of rotation. Built-in sigh window for optical regconignition of speed and direction of rotation and for stroboscopic scanning.....